2003
DOI: 10.1002/pon.718
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dyadic intervention on self‐efficacy, social support, and depression for men with prostate cancer

Abstract: Urinary and sexual dysfunctions are side effects of radical prostatectomy (RP) for prostate cancer (PC) that contribute to depression. Despite the effectiveness of support groups at reducing depression in cancer patients, men typically do not participate in them. The purpose of this pilot study was to test the effects of a dyadic intervention (one-to-one support) on social support (Modified Inventory of Socially Supportive Behaviors), self-efficacy (Stanford Inventory of Cancer Patient Adjustment), and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
180
1
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(207 citation statements)
references
References 45 publications
10
180
1
16
Order By: Relevance
“…Studies were conducted in Europe (n ¼ 5) (Burton et al, 1995;Marchioro et al, 1996;McArdle et al, 1996;Moynihan et al, 1998;Kuijer et al, 2004), the United States of America (n ¼ 8) (Evans and Connis, 1995;Sandgren et al, 2000;Antoni et al, 2001;Classen et al, 2001;Rawl et al, 2002;Winzelberg et al, 2003;Given et al, 2004;Weber et al, 2004) Canada (n ¼ 1) (Goodwin et al, 2001), Australia (n ¼ 3) (Edelman et al, 1999;McLachlan et al, 2001;Petersen and Quinlivan, 2002) and Japan (n ¼ 1) (Fukui et al, 2000). The mean sample size in the intervention and control group was 61 patients (range 15 -296) and 52 patients (range 15 -154), respectively.…”
Section: Psychotherapeutic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in Europe (n ¼ 5) (Burton et al, 1995;Marchioro et al, 1996;McArdle et al, 1996;Moynihan et al, 1998;Kuijer et al, 2004), the United States of America (n ¼ 8) (Evans and Connis, 1995;Sandgren et al, 2000;Antoni et al, 2001;Classen et al, 2001;Rawl et al, 2002;Winzelberg et al, 2003;Given et al, 2004;Weber et al, 2004) Canada (n ¼ 1) (Goodwin et al, 2001), Australia (n ¼ 3) (Edelman et al, 1999;McLachlan et al, 2001;Petersen and Quinlivan, 2002) and Japan (n ¼ 1) (Fukui et al, 2000). The mean sample size in the intervention and control group was 61 patients (range 15 -296) and 52 patients (range 15 -154), respectively.…”
Section: Psychotherapeutic Studiesmentioning
confidence: 99%
“…The proportion of female participants ranged from between 41 to 100%. Eight studies were multicentre trials (McArdle et al, 1996;Classen et al, 2001;Goodwin et al, 2001;McLachlan et al, 2001;Petersen and Quinlivan, 2002;Rawl et al, 2002;Given et al, 2004;Weber et al, 2004) and 10 were single-centre trials (Burton et al, 1995;Evans and Connis, 1995;Marchioro et al, 1996;Moynihan et al, 1998;Edelman et al, 1999;Fukui et al, 2000;Sandgren et al, 2000;Antoni et al, 2001;Winzelberg et al, 2003;Kuijer et al, 2004).…”
Section: Psychotherapeutic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that those cancer patients who feel more efficacious in their ability to cope are better adjusted (4,20), enjoy a higher quality of life (21), may live longer (22), and experience less depression (23) than those who feel less confident in their ability to cope.…”
mentioning
confidence: 99%
“…comm.). Several randomized controlled trials [17][18][19][20][21][22] investigated the effect of psychosocial intervention after treatment for prostate cancer on urinary bother [17][18][19][20][21][22], sexual bother [17][18][19]22], or sexual satisfaction [20,21,23]. Psychosocial intervention was associated with less sexual bother or higher sexual satisfaction in all but one study [17,18,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%